Interferon-inducible protein SCOTIN interferes with HCV replication through the autolysosomal degradation of NS5A - Nari Kim (Nature Portfolio, 2016)
Hepatitis C virus (HCV) nonstructural 5A (NS5A) protein is a critical factor for HCV RNA replication. Here the authors show that SCOTIN, an interferon beta-inducible host protein, functions to limit HCV replication by targeting viral protein NS5A for autophagosomal degradation.